Dramatic Intracerebral Hemorrhagic Presentations of Reversible Cerebral Vasoconstriction Syndrome: Three Cases and a Literature Review - Joel M. Stary; Bonnie H. Wang; Seong-Jin Moon; Huan Wang (Case Reports in Neurological Medicine)
Reversible cerebral vasoconstriction syndrome (RCVS) refers to a number of disorders characterized by severe and sudden-onset (“thunderclap”) headaches and angiographic features of reversible, segmental, multifocal vasoconstriction of cerebral arteries. Although RCVS generally resolves without significant sequelae, a rare and possibly underrecognized hemorrhagic presentation has a worse potential course. We report three cases of hemorrhagic RCVS and review the literature. Three females (42, 54, and 33 years old, resp.) presented with severe headache, neurological deficits, and dramatic intracerebral hemorrhage (ICH). Patient 1 presented comatose with a 9 × 4 × 6.6 cm left deep intraparenchymal hemorrhage (IPH) and 1 cm midline shift. She underwent emergent surgical intervention. Patient 2 had a 3.3 × 1.5 cm left superior frontal IPH that enlarged to 4 × 2.5 cm within 12 hours with worsening headache and neurological deficits. She was successfully managed nonoperatively. Patient 3, after uncomplicated pregnancy and delivery, presented with a 1.5 cm left superior parietal IPH on postpartum day 7. Two days later, she acutely developed right hemiplegia. Repeat CT demonstrated a new 3.3 × 1.7 cm left frontal IPH. She was also successfully managed nonoperatively. Many diverse conditions are grouped within the category of RCVS. Dramatic ICH remains a rare and possibly underrecognized presenting feature. Prompt diagnosis and management are essential for obtaining the best outcome.